LITERATURE REVIEW: METALLOTHIONEIN SEBAGAI PROTEIN PENGIKAT LOGAM UNTUK BIOREMEDIASI LOGAM BERAT - Ma'rifah, Amriyah Ummi; Anggraito, Yustinus Ulung; Setiati, Ning (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: The purpose of bioremediation is to remove or reduce dangerous compounds to improve environmental quality, one of which is heavy metals. Metal-binding proteins can minimize the impact of heavy metal pollution from the environment. This metal binding protein can accumulate metals by microorganisms. One of the known metal-binding proteins is metallothioneins (MTs). This protein can minimize the effects of heavy metals in the environment by creating protein-metal ion complex bonds. This review article provides a comprehensive insight into the role of metallothionein as a metal-binding protein for heavy metal accumulation, and the mechanisms involved in heavy metal bioremediation Methods: The method used is a literature review using reputable national and international journals. Results: Based on the results of a literature review, metallothionein can be found in many organisms such as bacteria, humans, plants, invertebrates, and mammals. Metallothionein can accumulate heavy metals that contain highly conserved cysteine residues. These residues allow MTs to bind, transport, and store various essential (Zn and Cu) and non-essential (Cd and Hg) heavy metals via thiolate bonding. Conclusion: Heavy metals are dangerous for the survival of living things and can cause damage to vital functions. One of the metal-binding proteins is metallothionein, which is involved in the organism's tolerance to heavy metal content and can accumulate it, so that the effects of heavy metals can be minimized.